Occupational exposure of pharmacy technicians and cleaning staff to cytotoxic drugs in Dutch hospitals. - Crul, Mirjam; Hilhorst, Simone; Breukels, Oscar; Bouman-d'Onofrio, Johanna R. C.; Stubbs, Percival; van Rooij, Joost G. (Journal of Occupational & Environmental Hygiene)
Many studies into surface contamination of hospital environments have demonstrated that occupational exposure to cytotoxics through the dermal route remains a possible risk. In this study, we assess the actual dermal exposure of the hands of pharmacy technicians and cleaning personnel in a panel of hospitals performing tasks that pose a risk of exposure. We compare the dermal exposure to a tentative limit value for cyclophosphamide. Pharmacy technicians and cleaning personnel were asked for hand rinsing after performance of nine tasks previously identified as posing a risk of occupational exposure. All samples were analyzed for the presence and quantity of eight antineoplastic drugs. By using data on both the frequency of the performance of the tasks and the measured dermal contamination during these tasks, weekly exposure to the marker drug (cyclophosphamide) was calculated. In five Dutch hospitals, 70 hand rinse samples and 8 blanks were collected. These were analyzed and results were used to calculate weekly exposure. The tentative limit value used was 0.74 µg of cyclophosphamide. For cleaning personnel, all results remained below this threshold value. For pharmacy technicians, the compounding itself also remained well below the limit; however, the task involving preparatory work, as well as the checking of compounded drugs, had a 13% chance of exceeding the limit. All of the highest values were found when employees were not wearing gloves on these tasks. Cleaning personnel and pharmacy technicians compounding cytotoxic drugs in our study were sufficiently protected from occupational exposure. In contrast, pharmacy technicians who perform preparatory and finishing tasks (before and after the actual compounding) are not protected enough when they do not wear gloves.